Absence of heterozygosity detected by single‐nucleotide polymorphism array in prenatal diagnosis. (7th January 2021) - Liu, J.; He, Z.; Lin, S.; Wang, Y.; Huang, L.; Huang, X.; Luo, Y.
ABSTRACT: Objectives: To investigate the general occurrence and clinical significance of absence of heterozygosity (AOH), detected by single‐nucleotide polymorphism (SNP) array on prenatal diagnosis. Methods: We recruited pregnancies undergoing invasive prenatal diagnosis at our fetal medicine center over a 6‐year period. All fetuses underwent SNP array using the Affymetrix CytoScan HD array platform. AOH was defined as a chromosomal homozygosity segment with neutral copy number. Cases with AOH over 10 Mb in size or with suspected pathogenicity were further analyzed, and the clinical features and outcome were reviewed. Results: Of 10 294 recruited fetuses, 100 (0.97%) with AOH were identified; in 81 (81.0%) of these, AOH occurred in a single chromosome, while 19 (19.0%) patients had multiple AOHs in different chromosomes. AOH was observed in all chromosomes, chromosomes X, 2 and 16 being the most frequently involved. The length of AOH ranged from partial chromosome (9.002–80.222 Mb) to the entire chromosome. Similar AOH regions displayed varied clinical manifestations. In total, 55 patients presented with concomitant ultrasound abnormalities, the most common being multiple abnormalities (14/55 (25.5%)), genitourinary malformations (8/55 (14.5%)), skeletal malformations (5/55 (9.1%)) and small‐for‐gestational age (5/55 (9.1%)). Notably, the rate of adverse perinatal outcome (including termination of pregnancy, neonatal death, fetal death, selective reduction and miscarriage) in fetuses with AOH and ultrasound abnormalities (30/48 (62.5%)) was higher than in those without ultrasound abnormalities (6/40 (15.0%)) ( P  < 0.001). Further non‐invasive prenatal testing using cell‐free fetal DNA from maternal blood indicated chromosomal copy number abnormalities in 11 patients; however, they were confirmed as AOH by SNP array of the amniotic fluid. Conclusions: Genetic counseling regarding a prenatal diagnosis of AOH remains challenging. To evaluate comprehensively its significance, we propose a management strategy involving further serial ultrasound examinations, parental verification, whole‐exome sequencing, placental study and effective follow‐up. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.